2020
DOI: 10.1002/naaq.10141
|View full text |Cite
|
Sign up to set email alerts
|

Early Weaning Effects on Survival, Growth, and Histopathology of Larval Sterlet Acipenser ruthenus

Abstract: Weaning of fish is a critical stage during larval rearing and could cause high mortality. Therefore, proper larval weaning period selection is crucial for the success of larviculture. This study aimed to find the effect of weaning on growth performance, histopathological features, and mortality rates in larvae of Sterlet Acipenser ruthenus. The experimental rearing was conducted from 7 to 38 d posthatch (dph) at a mean temperature of 18°C in a recirculating system. The experiment was carried out in three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…El-Dahhar et al (2016b) found the same significance in terms of FBW, (WG), (ADG) and (SGR, %) for sea bass weaned with MD obtained in 42 and 57 DPH at different weaning periods (P <0.05). In addition, the results of this study are consistent with the approaches of (Suzer et al, 2007;Laczynska et al, 2020) who believed that MD inclusion can be started after 25 dph. The 15-day group (dph) of D. labrax larvae culture had the lowest growth and survival rates, while the 25-day group (dph) had the highest.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…El-Dahhar et al (2016b) found the same significance in terms of FBW, (WG), (ADG) and (SGR, %) for sea bass weaned with MD obtained in 42 and 57 DPH at different weaning periods (P <0.05). In addition, the results of this study are consistent with the approaches of (Suzer et al, 2007;Laczynska et al, 2020) who believed that MD inclusion can be started after 25 dph. The 15-day group (dph) of D. labrax larvae culture had the lowest growth and survival rates, while the 25-day group (dph) had the highest.…”
Section: Discussionsupporting
confidence: 92%
“…Formulated food should not be used to substitute Artemia for daily use suddenly, but should start with mixed feeding, by decreasing daily live food and gradually increasing formula feed, till proceed as it is completely replaced (Portella and Dabrowski 2008;Laczynska et al, 2020). In this combined feeding method was longly known as co-feeding strategy, the growth rate may be similar or better than that of Artemia feeding alone (Person Le Ruyet et al, 1993).As previously reported by Taylor et al 2020, who pointed out that, MD is appropriate for larval growth , should have high platability, and have high stability in seawater, and it easily classify them as Suitable size, can be used in automatic feeders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laczynska et al. (2020) conducted a weaning trial on Sterlet Acipenser ruthenus larvae and found that fish increase wet body weight and total length and develop a better liver and digestive tract when the larvae were fed Artemia nauplii at 7–15 dph. Kolkovski et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many aquaculture facilities use live feeds such as rotifers ( Brachionus plicatilis ) and brine shrimp ( Artemia franciscana ) nauplii for their larval fish diets (Laczynska et al. 2020). Compared to formulated diets, live prey comprises a significant portion of the financial and logistical costs in fish culturing.…”
Section: Experimental Stage Age Range (Dph) Tank Size Target Density ...mentioning
confidence: 99%